Faktor Risiko Diabetes Melitus Tipe-II Pada Remaja - Sanjaya, Lalu Rodi; Yana Setiawan (Citra Delima Scientific journal of Citra Internasional Institute, 2024)
Diabetes Mellitus (DM) is a non-communicable chronic (chronic) disease and is still a big problem in the world. DM is not only experienced by adults but also by teenagers. Most of the risk factors for DM can be modified, so researchers are interested in conducting this research as early as possible among teenagers. This study aims to analyze risk factors for DM in adolescents. The research is a type of quantitative research with a correlational analytical design. The population of class X-XI students with a sample of 100 people. Data was collected using a questionnaire and analyzed using SPSS computerized assistance. Statistical analysis used chi-square to assess the relationship between nutritional status variables and the GDS value (p-value=0.294) and the relationship between activity patterns and the GDS value, namely (p-value=0.780). The conclusion in this study is that there is no relationship between nutritional status and activity patterns and GDS scores in adolescents.